Efficient DNA extraction from cytogenetic suspensions: A new possibility for obtaining DNA, with potential applications in studies of molecular markers - Geórgia Liz Monteiro Sant’ana-Arruda; Paulo Cesar Venere; Daniela Cristina Ferreira (PLoS ONE, 2025)
The present study demonstrates the viability of extracting DNA for genomic analyses from cell suspensions prepared for cytogenetic analyses, specifically, samples fixed in Carnoy’s solution (3:1 methanol: acetic acid) and stored at –20 °C for more than 10 years. Cell suspensions from 27 specimens of fish of the subfamily Loricariinae, which had been prepared originally for cytogenetic studies, were used to test a DNA extraction procedure based on a routinely-used protocol with specific minor adjustments. The spectrophotometric and electrophoretic analyses of the extracted samples revealed DNA at good concentrations (5.9–1739 ng.μL -1 ) and high purity (A260/A280 ratios of 1.75–2.07), indicating negligible contamination and no significant fragmentation. The integrity of the material was confirmed by the successful amplification by PCR of four different genes (COI, 5S, 18S, and RAG2), with the COI gene being sequenced efficiently. These results demonstrate that DNA can be extracted from samples collected for other purposes, even after long-term storage, producing high-quality genomic DNA from sources that might otherwise be overlooked. The exploitation of these samples as a source of DNA represents a useful potential strategy for the acquisition of material for analysis when fresh samples are scarce or difficult to obtain. This novel approach expands considerably the possibilities for retrospective molecular studies, especially in the fields of conservation and systematics.